The landscape of tumor cell states and spatial organization in H3-K27M mutant diffuse midline glioma across age and location - Ilon Liu; Li Jiang; Erik Samuelsson; Sergio Marco Salas; Alexander Beck; Olivia A. Hack; Da-Eun Jeong; McKenzie Shaw; Bernhard Englinger; Jenna LaBelle; Hafsa M. Mire; Sibylle Madlener; et al. (2022)
Abstract Histone 3 lysine27-to-methionine (H3-K27M) mutations most frequently occur in diffuse midline gliomas (DMGs) of the childhood pons but are also increasingly recognized in adults. Their potential heterogeneity at different ages and midline locations is vastly understudied. Here, through dissecting the single-cell transcriptomic, epigenomic and spatial architectures of a comprehensive cohort of patient H3-K27M DMGs, we delineate how age and anatomical location shape glioma cell-intrinsic and -extrinsic features in light of the shared driver mutation. We show that stem-like oligodendroglial precursor-like cells, present across all clinico-anatomical groups, display varying levels of maturation dependent on location. We reveal a previously underappreciated relationship between mesenchymal cancer cell states and age, linked to age-dependent differences in the immune microenvironment. Further, we resolve the spatial organization of H3-K27M DMG cell populations and identify a mitotic oligodendroglial-lineage niche. Collectively, our study provides a powerful framework for rational modeling and therapeutic interventions.